Associação entre fenótipos de frênulos orais, contraturas congênitas e disfagia em crianças com síndrome congênita do Zika vírus - Cavalcante, Grisielle Mary Ferreira de Sá (2022)
Around 2015, Zika virus infection during the prenatal period was associated with poor outcomes such as microcephaly and other serious brain abnormalities. Infection by this virus has become a concern, gaining international attention, due to an apparent 20-fold increase in the incidence of microcephaly during an outbreak of this disease in Brazil. Later studies concluded that the phenotype presented not only involved microcephaly, but constituted a new pattern of birth defects, called congenital Zika syndrome (CZS). Previously, a cross-sectional study showed that individuals affected by CZS have a higher prevalence of posteriorly positioned or submucosal lingual frenulum. However, the present dissertation aimed to evaluate the oral frenulum of children with CZS and to evaluate possible associations between neurological alterations and the oral frenulum phenotypes observed in this population. The present work has a longitudinal design, as part of a broader multidisciplinary cohort project. The final study sample consisted of 63 children diagnosed with CZS, aged between 1 and 20 months of both sexes. Data collection was carried out at four different times, spread over a period of 30 months. Thirty-one healthy children, in the same age group, of both sexes made up the control group. The babies underwent thorough clinical and neurological evaluations by a multidisciplinary team. Then, data collection included intraoral anatomical assessments performed by a pediatric dentist. The lingual frenulum was evaluated observing the following aspects: visibility, thickness, and level of fixation. The labial frenulum was examined by moving the upper and lower lips apart, followed by bidigital pressure. The protocols of Coryllos et al. (2004) and Kotlow (2013) for the classification of lingual and labial frenulum respectively. The association between categorical variables such as dysphagia (presence/absence), congenital contractures (presence/absence), type of lingual frenulum, type of upper labial frenulum, type of lower labial frenulum were tested by chi-square and Fisher's exact tests. The significance level was set at p < 0.05. A significant number of children with CZS have the superior labial frenulum inserted into the papilla region extending to the palate region (p = 0.0008) and a significant association between this type of frenulum and the absence of congenital contracture (p = 0.0435). Children with CZS had lower labial frenulum frequently inserted in a V (p = 0.001), and a significant association was observed between this type of frenulum and the presence of dysphagia (p = 0.0278). The present study expanded the understanding of the most prevalent phenotypes of oral frenulum in children affected by CZS and demonstrates the existence of an association between the phenotypic pattern of oral frenulum and neurological alterations observed in that syndrome. These findings may help to predict the neurological manifestations of CZS and indicate the need to evaluate a greater number of affected patients to establish protocols and predict the risk of the emergence of such neurological alterations based on the oral frenulum.